Pengaruh Model Pembelajaran The Larning Cell (Sel Belajar) Terhadap Hasil Belajar Sosiologi Kelas XI IPS 1 SMA Negeri 1 Tigo Nagari Kabupaten Pasaman - Noni, Noni; Melia, Yeni; Hefni, Hefni (Jurnal Pendidikan Tambusai, 2021)
This reseach background is by low learning outcomes in SMA N 1 Tigo Nagari, Kabupaten Pasaman because many students are just silent and do not want to answer the questions given by the teacher, when given individual training students often neglect the tasks given by the teacher. The purpose of research is to know whether be the effect of learning application Cell learning on learning outcomes on social problem material in class XI of SMAN 1 Tigo Nagari, Kabupaten Pasaman. That used in this research was kognitivisme theory to Jean Piaget. The Method used real experiment design with class experiment and class control posttest. Sampling was done by purpose sampling with sample completely 52 students, 27 students class experiment and 25 class control. Data were obtained from posttest in the from of multiple choice as many as 20 questions. The data analysis of the two group using t-test independent test and Regresi Linier Simple Test. The result of data analysis shown that the average learning outcomes of sociology students that apply cell learning was 79,81and the avarege of learning outcomes sociology students that does not apply cell learning was 71,8 with value Sig (2-tailed) < 0.05 (0.003 < 0.05). This research shown there is impact of cell learning toward learning outcomes of students.